2024
DOI: 10.3390/ani14060856
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Virulence Potential of Bacterial Species from Captive Birds of Prey—Consequences of Falconry for Public Health

Rita Magalhães,
Luís Tavares,
Manuela Oliveira

Abstract: Falconry has been practiced for thousands of years and is nowadays frequently employed in activities such as pest control, hunting, falcon racing, and environmental education. Antimicrobial resistance levels have risen in the past years, constituting an emerging global problem with a direct impact on public health. Besides both topics being studied on their own, information on the role of captive birds of prey in the potential dissemination of virulence factors and antimicrobial resistance determinants of bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Captivity plays a fundamental role in influencing the oral and intestinal microbiome of hosted birds of prey and is also associated with high rates of antibiotic resistance, compared to free-living birds [ 38 ]. This change can already occur after a month of direct contact between animals and humans, and the diet, especially if based on raw food, represents the first determining causal factor [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Captivity plays a fundamental role in influencing the oral and intestinal microbiome of hosted birds of prey and is also associated with high rates of antibiotic resistance, compared to free-living birds [ 38 ]. This change can already occur after a month of direct contact between animals and humans, and the diet, especially if based on raw food, represents the first determining causal factor [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This change can already occur after a month of direct contact between animals and humans, and the diet, especially if based on raw food, represents the first determining causal factor [ 39 , 40 , 41 ]. Some studies have shown that birds of prey fed poultry meat develop a wider range of Gram-negative bacterial flora [ 38 ]; in particular, a study on falcons has shown that the diets most commonly fed to these birds increase the levels of Salmonella in the intestinal flora [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation